John Milton's 'Paradise lost' : a reading guide - Reisner, Noam, 1974- (Edinburgh : Edinburgh University Press, 2011)
Noam Reisner leads readers through the complexities of Milton's celebrated and challenging narrative poem as well as introducing them to the key critical views. The guide combines an introduction to the poem's main thematic and stylistic concerns together with discussion of important selected passages (substantial extracts from the text are included) and provides readers with a basic set of critical tools with which to interpret the text. Key Features Detailed discussion of select passages from the poem divided into three interrelated sections - 'concepts and themes', 'style and form' and 'historical-political context' - for easy reference Provides a general guide to teaching the text - first time teachers will find many suggestions for teaching as well as templates for teaching the poem in different course formats Up-to-date annotated bibliography
Cover; Copyright; Contents; Preface; Series Editors' Preface; Chapter 1 Mapping and Making Paradise Lost; Chapter 2 Text, Commentary and Analysis; Chapter 3 Teaching the Text; Bibliography; Index.
Includes bibliographical references (pages 153-162) and index.
Print version record.
English.
JSTOR
Keywords: Milton, John, -- 1608-1674.; Milton, John, -- 1608-1674 -- Criticism and interpretation; Milton, John, -- 1608-1674; Paradise lost (Milton, John); Milton, John, -- (1608-1674) -- Critique et interprétation.; English literature -- 17th century -- History and criticism; English literature -- Early modern, 1500-1700 -- History and criticism; Littérature anglaise -- 17e siècle -- Histoire et critique; POETRY -- English, Irish, Scottish, Welsh; LITERARY CRITICISM -- Middle Eastern; English literature; Paradise lost (Milton); 1600-1699; Criticism, interpretation, etc